VAKSIN UNTUKKU, UNTUKMU, DAN KITA SEMUA “AYO VAKSINASI COVID-19” - Krisnawati, Monik (ABDIMAS Madani, 2022)
Covid-19 is a disease that attacks the respiratory system and has recently spread to various countries in the world. The risk of death from the disease caused by infection with the SARS-Cov-2 virus is known to increase if it is accompanied by other comorbidities. With the Covid-19 pandemic, the government has set a policy of limiting all social activities and implementing a vaccination program to reduce and prevent the possibility of transmitting Covid-19 to the community. On the other hand, the Covid-19 pandemic and various infodemic circulating in the community have triggered public doubts about various information received from the government in tackling the transmission of Covid-19. Most of the population in Gilangharjo Village still have a traditional lifestyle and very few residents are educated to college so that people find it difficult to sort out information according to scientific facts. This causes public perception of the Covid-19 pandemic and the programs provided to deal with the pandemic are only considered as less important to be studied. and discussion. The technical implementation is carried out at one time, namely on October 9, 2021. The results of the activities that have been carried out show that most of the PKK women who are the object of the activity, so far have not fully understood the Covid-19 vaccine. Activity participants were greatly helped by providing counseling to increase knowledge and awareness of the importance of Covid-19 vaccination.